Personal Identification using the Distance and Triangle between the Metacarpophalangeal Joints - Srathongkro, Siwa; Kaewjumras, Yongyut; Ngamsapmanee, Wanasanan; Somdock, Nuttakrit; Sawangjit, Nalita; Klongratog, Bhanupol (Science Essence Journal, 2022)
Personal identification using the distance among the metacarpophalangeal joints (MCPs) was presented in this study. The system was developed to specify the dorsal hand patterns. Firstly, the dorsal hand images were taken for the subjects via an infrared camera. Secondly, the dorsal hand images were converted to grayscale and binary images using image processing techniques. After that, the distance of the MCPs was measured by various the dorsal hand images including index to middle, middle to ring, ring to little, and index to little of the dorsal hand. In addition, the triangle areas between index to middle, middle to ring, ring to little, and index to little of the dorsal hand were used to specify the dorsal hand patterns. The result of the distance and the triangle area of the MCPS can be used to identify a person because of the difference of distance and the triangle area of the MCPs of each person.